Berdakwah dengan Narasi: Studi Kisah-Kisah Abu Nawas - Indrawati, Indrawati; Harianto, Yudi Asmara (STID Al-Hadid, 2024)
The stories of AbuNawas has long been known as a bedtime story. Not many people realize that in thestory of Abu Nawas there is da'wah message that fits the context of the golden ageof Islam, especially during the time of the caliph Harun Al-Rasyid. To find out thecontent of the da'wah message, it is necessary to analyze the narrative flow in AbuNawas' stories. This article aims to provide a complete picture of the narrative flowor plot of the Abu Nawas stories. The research method uses a descriptive qualitativeapproach using Tzetan Todorov's narrative structure theory and ChristopherBooker's narrative plots. Data was taken from 27 stories in the book entitled 'TheStory of 1001 Nights: Abu Nawas the Heartbreaker'. The resulting conclusion showsthat the narrative flow of the Abu Nawas stories are different from Todorov andBooker's theory. The stories of Abu Nawas have a storyline that begins with thepresence of a problem, attempts to think of solution, and finally the problem issolved. The plot in the stories of Abu Nawas also illustrates the ingenuity of a Muslimin dealing with problems no matter how difficult they are. The conclusion of thisarticle can be an inspiration for preachers who use the bil qalam path.